Estudio Geológico-Estructural e inventario de deslizamientos del Área 3 de la cuenca de Loja - Ambuludi Arcentales, Henry Rabindranath (2015)
The Degree of Geology and Mines of the Technical University of Loja boost this Survey Geological-Structural and inventory of landslides Area three (3) of the basin of Loja, in an area of 2900 hectares, in order to have information updated and define in a better way the contacts of different geological formations and their structural and tectonic elements that help define the geological and tectonic structure of the entire sedimentary basin of Loja. The investigation began with the description of the project, comprising; geographical location, accessibility, climate and hydrography, then the geological field research was developed, with the description of geological outcrops and structural data, and proceeded to perform the geological survey of the area. Finally the interpretation of results was performed to define the geological units present, contacts, lithology, structure and correlated with the regional geological map of Hungerbühler et al.,2002. The landslide inventory was also conducted to define their conditioning and triggering factors.